Otimização da extração de azeite de azeitona Cobrançosa por adição de adjuvantes tecnológicos - Peres, F. (2012)
Modelling and optimization of the operation conditions of olive oil extraction were performed, using surface response methodology, following a central rotation composite matrix, as a function of the contents of enzymes (Endozym Olea AS; 0.04- 0.24%) and natural microtalc (FC8-AW; 0.12-0.68%) added at the beginning of the thermobeating step. Yield was evaluated by the extractability index and by the residual pomace fat content. The obtained results showed that the extraction yield depends on the amount of talc used but does not depend on the amount of enzyme added, within the tested range. Also, the presence of these processing aids did not affect either quality parameters or the content of green pigments in the obtained olive oils.